CONSUMER PROTECTION IN BULGARIA: EU CHALLENGES - Corina, Ene (Economics of Agriculture, 2012)
Consumer protection represents today a key-concern for each modern economy, as it reflects its potential of providing well-being for citizens and of empowering them to act efficiently on the markets. In the European Union, consumer policy for 2007-2013 address several challenges, including those related to the extension of the EU, given the discrepancies between Member States. This paper aims to underscore challenges that Bulgaria is facing today in the European context, based on relevant data resulting from surveys and reports. It also suggests several steps to be undertaken in the pursuit of better consumer protection at national level.